Adaptation of fluid model EULAG to graphics processing unit architecture. (14th October 2014) - Rojek, Krzysztof Andrzej; Ciznicki, Milosz; Rosa, Bogdan; Kopta, Piotr; Kulczewski, Michal; Kurowski, Krzysztof; Piotrowski, Zbigniew Pawel; Szustak, Lukasz; Wojcik, Damian Karol; Wyrzykowski, Roman; Hussain, Farookh Khadeer; Wyrzykowski, Roman; et al.
Summary The goal of this study is to adapt the multiscale fluid solver EULerian or LAGrangian framewrok (EULAG) to future graphics processing units (GPU) platforms. The EULAG model has the proven record of successful applications, and excellent efficiency and scalability on conventional supercomputer architectures. Currently, the model is being implemented as the new dynamical core of the COSMO weather prediction framework. Within this study, two main modules of EULAG, namely the multidimensional positive definite advection transport algorithm (MPDATA) and the variational generalized conjugate residual, elliptic pressure solver Generalized Conjugate Residual (GCR) are analyzed and optimized. In this paper, a method is proposed, which ensures a comprehensive analysis of the resource consumption including registers, shared, and global memories. This method allows us to identify bottlenecks of the algorithm, including data transfers between host and global memory, global and shared memories, as well as GPU occupancy. We put the emphasis on providing a fixed memory access pattern, padding as well as organizing computation in the MPDATA algorithm. The testing and validation of the new GPU implementation have been carried out based on modeling decaying turbulence of a homogeneous incompressible fluid in a triply‐periodic cube. Simulations performed using the standard version of EULAG and its new GPU implementation give similar solutions. Preliminary results show a promising increase in terms of computational efficiency. Copyright © 2014 John Wiley & Sons, Ltd.